Relationship between students' faith and habits with certain parameters and participation in additional physical activities after school: Pilot research - Bubnjević Ksenija V.; Milošević-Stolić Jasmina; Glavač Boris (University of Kragujevac - Faculty of Pedagogy, Užice, 2022)
School-age children are recommended to participate in physical activities for at least 60 minutes daily. It is considered that half of that time should be used for physical activities at school where children spend a lot of time. It has been emphasized that motivation for active participation in physical education decreases during schooling. Family habits are considered to be very important and have an impact on the active participation of a child in physical education as well as in all other forms of physical activity. The aim of the present pilot research was to indicate the possible relationship between variables that have an impact on students' motivation (BMI, physical exercise motivation, healthy habits concerning healthy diet and sleeping, parental sports habits, family beliefs and devotion or child's acquired internal beliefs) and their active participation in any of extracurricular sport activities. The survey of parents (N = 12) whose children are at primary school was conducted. It was found that children (aged 7-14) have optimal BMI values (16.3 kg / m2). It also showed that each child is involved in some sport activity. It was estimated that every child takes enough fruit/vegetables per day, as well as sweets. Children sleep enough (9 hours a day). When asked about faith (belief), the parents referred to faith in "God" or belief in "Self". It can be concluded that there is very little interest in free sport activities. At the same time, the parents prefer sport activites organized outside the school.